Nonlinear vs. linear biasing in Trp-cage folding simulations - Spiwok, Vojtěch; Oborský, Pavel; Pazúriková, Jana; Křenek, Aleš; Králová, Blanka (The Journal of chemical physics, 2015)
Biased simulations have great potential for the study of slow processes, including protein folding. Atomic motions in molecules are nonlinear, which suggests that simulations with enhanced sampling of collective motions traced by nonlinear dimensionality reduction methods may perform better than linear ones. In this study, we compare an unbiased folding simulation of the Trp-cage miniprotein with metadynamics simulations using both linear (principle component analysis) and nonlinear (Isomap) low dimensional embeddings as collective variables. Folding of the mini-protein was successfully simulated in 200 ns simulation with linear biasing and non-linear motion biasing. The folded state was correctly predicted as the free energy minimum in both simulations. We found that the advantage of linear motion biasing is that it can sample a larger conformational space, whereas the advantage of nonlinear motion biasing lies in slightly better resolution of the resulting free energy surface. In terms of sampling efficiency, both methods are comparable.
Keywords: chemické modely; Computer Simulation; lineární modely; Proteins; pohyb těles; Protein Folding; Motion; počítačová simulace; Solvents; Models, Chemical; sbalování proteinů; proteiny; Nonlinear Dynamics; Linear Models; rozpouštědla; nelineární dynamika